Outcomes of Nitinol Compression Staples in Tarsometatarsal Fusion - Carissa C. Dock BS; Katie L. Freeman MD; J. Chris Coetzee MD; Rebecca Stone McGaver MS, ATC; M. Russell Giveans PhD (Foot & Ankle Orthopaedics, 2020)
Background: Tarsometatarsal (TMT) arthrodesis is commonly performed in the management of midfoot arthritis, trauma, or deformity. The purpose of this study was to collect aggregate data (demographic, surgical, and perioperative outcomes) on patients who previously had a TMT fusion with BME compression staples. Methods: Sixty-six patients underwent TMT fusion with BME compression staples. Outcomes included demographics, surgical information, the Veterans Rand VR-12 Health Survey, Foot and Ankle Ability Measure (FAAM), visual analog scale (VAS), Revised-Foot Function Index (FFI-R), Ankle Osteoarthritis Scale (AOS), patient satisfaction survey scores, radiographic fusion rate, level of pain reduction, and complications. Sixty-six patients (68 feet) were analyzed (59 females) with an average age of 64 years (range, 18-83). The mean latest follow-up was 35.9 (range, 6-56.6 months). Results: The average surgical time was 38.1±14.3 minutes (range, 11-75). All outcomes improved significantly ( P < .001) from preoperative to latest follow-up except for the VR-12 Mental and Physical score. The average time to fusion determined by radiographs was 8.4 weeks (range, 6.1-46.1 weeks). Wound complications were not seen. Indications for subsequent surgeries (26.5%, 18/68 feet) in this current study included pain (n = 14), broken staples, and nonunion (n = 3). Conclusions: The fusion rate in this study, 89.7%, was similar to values reported in the literature. The patient satisfaction score of 81.9 at latest follow-up is consistent with patient satisfaction for other methods of fusion. Level of Evidence: Level IV, retrospective case series.